PENYELESAIAN SENGKETA PENANAMAN MODAL ASING DI BALI - Desi Miari, Ni Komang; Wiryawan, I Wayan; Westra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015, 2015)
The title of this legal research is the Settlement of Foreign Investment in Bali.The problem of how form - the form of foreign investment dispute resolution. In thesubsequent description will also be discussed whether the constraints faced in thesettlement of foreign investment disputes. The purpose of this study was to determine theprocedures or forms of dispute resolution foreign investment in Bali. And to know andunderstand what are the constraints faced in the settlement of foreign investmentdisputes in Bali. Type used in this paper is an empirical legal research. Data collectiontechniques used are collecting secondary data and primary data. The type of approachused is the collection of field data obtained from interviews and literature study. Theconclusion of this research is a form of dispute resolution foreign investment in Bali canbe divided into 2 (two), namely by way of litigation and non-litigation. And constraintsin the settlement of foreign investment disputes through litigation, the court there was atrend favoring the national party, and in addition it is also the process of disputeresolution through the courts deemed too long so it is not efficient in terms of both timeand cost. When the settlement of foreign investment disputes through non-litigation, isthe most fundamental constraints on the implementation of the decision of thearbitration forum in which foreign arbitration award is preventive and not binding.
Keywords: Resolution, Dispute, Forms, Constraints